Mapping Indonesian EFL Teachers’ Perception and Practice of Technology Integration - Setyaningsih, Endang; Wahyuni, Dewi Sri; Rochsantiningsih, Dewi (Kantor Jurnal dan Publikasi Universitas Pendidikan Indonesia, 2020)
The growing number of 2.0 studies indicated the increasing tendency to integrate technology into EFL teaching. Reports on teachers' perception of and practice of technology integration can easily be found in research databases. Nevertheless, quite a few laid attempts to map and build a tentative connection between perception and practice. This study examined teachers' current practice and their perception of technology integration. The respondents of this study were 40 English teachers from 20 senior high schools in a district in Indonesia. To collect the data, a technology integration questionnaire (TIQ) was developed based on pre-existing instruments. The responses were analyzed using both quantitative and qualitative strategies. The study found that, first, the teachers commonly held positive views on the use of technology although they also indicated their alert on the challenges and requirements for the success of the implementation. Second, the responses suggested that there was a connection between teachers' perception and their technology integration practice. Third, viewed from the SAMR model, the teachers' technology integration practice mainly fell into substitution and augmentation. Categorization of the technology integration purpose, practice, and process is discussed further. The study concludes teachers’ practice tended to focus more on the technology but less on the teaching and learning.